334 Pet food safety: truth in labeling. (30th November 2020) - Edwards, David; Conway, Charlotte
Abstract: In the United States, substances intended for use in animal foods are generally considered to be either animal foods or animal drugs. The regulatory classification of a substance relies on its intended use. Claims for substances that are regulated as animal foods are limited to those that can be attributed to the substance's "food" properties, which the courts in the United States have defined as being related to the provision of nutritive value, taste, or aroma or for a technical effect on the food itself. Any substance intentionally added to an animal food must be either an approved food additive as listed in part 573 in Title 21 of the Code of Federal Regulations (21 CFR 573) or a substance that is generally recognized as safe (GRAS) for an intended use, including those listed in 21 CFR 582 and 584. Also, in coordination with state feed control officials, CVM recognizes ingredients in the Official Publication of the Association of American Feed Control Officials (AAFCO) as being acceptable for use in animal foods. Everything on a pet food label must be truthful, not misleading, and appropriate for a product regulated as food. Federal regulations (21 CFR 501) require that labels include: an appropriate product name, all ingredients in descending order of predominance by weight, a statement of net quantity of contents, and the address of manufacturer or distributor. Most states have additional labeling requirements. Studies conducted for scientific research need to be evaluated to determine if the endpoints and parameters measured are also appropriate as regulatory data. Feeding studies may address target animal safety and/or utility of the substance for its intended use as a food. CVM will provide written feedback on protocols intended to address new feed ingredients.